OVERVIEW OF PATIENT COMPLIANCE IN THE USE OF TUBERCULOSIS DRUGS IN THE WORKING AREA OF THE LUBUK ALUNG HEALTH CENTER, PADANG PARIAMAN DISTRICT, 2O22 - Sarah Mailisa, Sarah; Reslina, Isra; Elvina, Ridha; Widya, Nurul; Rosa, Rida (Indonesian Journal of Pharmaceutical Research, 2024)
Tuberculosis (TB) cases are one of the health problems experienced by many Indonesian people. Tuberculosis (TB) is an infectious disease, in Padang Pariaman Regency in 2021 to 2022 it will experience an increase where in 2022 Lubuk Alung sub-district will be recorded as the area with the highest TB cases. This study aims to look at the characteristics and adherence to the use of TB drugs. The data collection method in this study was total sampling where the total number of respondents was 63 people. With the results of the study that the characteristics of the respondents, the sex most affected by TB was male, namely 52.6%, the highest education was high school, 65.8%, and the most common jobs were in other categories (workers, traders, drivers students), namely 50%. Meanwhile, the highest income is 1000000, which is 52.6%, and the distance from home to health services is the highest, which is 5KM, namely 65.8%. Meanwhile, for adherence to the use of TB itself, tuberculosis patients in the working area of the Lubuk Alung Health Center are categorized as high, with a percentage of 36.9%.Keywords: Tuberculosis, Compliance, use of Tuberculosis Drugs